2009
DOI: 10.1111/j.1528-1167.2008.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitric oxide, superoxide anion, and peroxynitrite to activation of mitochondrial apoptotic signaling in hippocampal CA3 subfield following experimental temporal lobe status epilepticus

Abstract: Summary Purpose:  One cellular consequence of status epilepticus is apoptosis in the hippocampal CA3 subfield. We evaluated the hypothesis that the repertoire of cellular events that underlie such elicited cell death entails mitochondrial dysfunction induced by an excessive production of nitric oxide synthase II (NOS II)‐derived NO, increased superoxide anion (O2−) production, and peroxynitrite formation. Methods:  In Sprague‐Dawley rats, kainic acid was microinjected unilaterally into the hippocampal CA3 subf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(111 citation statements)
references
References 52 publications
2
109
0
Order By: Relevance
“…The different onset of caspase 3 activation in CA1, CA3 and DG-hilus may due to that CA3 is highly accessible to KA-mediated excitotoxicity [38]. A similar nuclear activation of caspase 3 in neurons has been described previously [49,50]. Those studies suggested that SE-mediated nuclear caspase 3 activation may activate caspase-activated DNase (CAD) results in DNA fragmentation and apoptosis [51].…”
Section: Discussionmentioning
confidence: 69%
“…The different onset of caspase 3 activation in CA1, CA3 and DG-hilus may due to that CA3 is highly accessible to KA-mediated excitotoxicity [38]. A similar nuclear activation of caspase 3 in neurons has been described previously [49,50]. Those studies suggested that SE-mediated nuclear caspase 3 activation may activate caspase-activated DNase (CAD) results in DNA fragmentation and apoptosis [51].…”
Section: Discussionmentioning
confidence: 69%
“…For this purpose, 10-lm paraffin-embedded brain sections were deparaffinized in two exchanges of xylene for 5 min each, washed sequentially in 100%, 95%, and 70% ethanol, and stained with cresyl violet (Chen et al, 2006;Chuang et al, 2009). Pyramidal neurons were counted in a double-blind manner in the middle CA1 region of the hippocampus.…”
Section: Double Immunofluorescence Staining and Laser Confocal Microsmentioning
confidence: 99%
“…Western blot analysis for PGC-1a, UCP2, or SOD2 subunits was carried out on proteins extracted from total lysate or nuclear fractions of hippocampal samples Chen et al, 2006;Chuang et al, 2009). The primary antisera used included a rabbit polyclonal antisera against PGC-1a or SOD2 (Santa Cruz Biotechnology, Santa Cruz, CA), or goat polyclonal antiserum against UCP2 (Santa Cruz Biotechnology), or mouse monoclonal antiserum against atubulin (Santa Cruz Biotechnology).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In addition, CoQ10 could protect hippocampal neurons against kainate neurotoxicity (Won et al 2011) and its local application is capable to blunt cellular events leading to apoptosis and cell death in hippocampal CA3 subfield following status epilepticus (Chuang et al 2009). On this foundation, this compound may be a good candidate for neuroprotection against kainateinduced excitotoxic insult.…”
Section: Introductionmentioning
confidence: 98%